Collected Writings of Sir Robert Jennings, Volume 1 : Foreword by Professor Georges Abi-Saab - Jennings, Sir Robert Y., (International Law - Book Archive pre-2000., 1998)
The print edition is available as a set of two volumes (9789041111081).